1998
DOI: 10.1097/00002060-199809000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Treatment of Shoulder Subluxation in Hemiplegia

Abstract: Shoulder subluxation in hemiplegic patients has been recognized as a difficult problem to manage. In the study contained herein, our aims are to evaluate shoulder subluxation, to clarify if shoulder subluxation causes pain, and to discuss the treatment of shoulder subluxation. The study included 75 hemiplegic patients with shoulder subluxation. Each patient was evaluated for the degree of shoulder pain, motor recovery of the upper limb, and shoulder range of motion. Some indexes for evaluating subluxation were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
81
0
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 7 publications
3
81
0
6
Order By: Relevance
“…5 These clinical entities, however, are likely end products of a complex cascade of events initiated by the biomechanical compromise of the poststroke glenohumeral joint. 6 Although arthrograms have been used to evaluate structural abnormalities in the painful poststroke shoulder, [7][8][9][10][11][12] the results of these studies have been inconsistent.…”
mentioning
confidence: 99%
“…5 These clinical entities, however, are likely end products of a complex cascade of events initiated by the biomechanical compromise of the poststroke glenohumeral joint. 6 Although arthrograms have been used to evaluate structural abnormalities in the painful poststroke shoulder, [7][8][9][10][11][12] the results of these studies have been inconsistent.…”
mentioning
confidence: 99%
“…Lo et al 8) revealed eleven causes of shoulder pain when they examined patients within two months after stroke using arthroscopy. According to their study, 50% of the patients suffered adhesive capsulitis, and the incidence rate within one year reached 74% 9) . In a stable condition, shoulder pain showed a significant correlation with the joint range of motion of the affected shoulder external rotation 3) , and the affected shoulder external rotation is related to the time (r=-0.538) since stroke attack 8) .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Current clinical methods include palpation, the number of finger-breaths, and use of thermoplastic jigs. However, these clinical methods are physician-dependent with low sensitivities.…”
mentioning
confidence: 99%
“…Although radiographs have high reliability and validity, they have some disadvantages such as high cost, and being time-consuming and radiation exposure. [8][9][10][11] On the other hand, musculoskeletal ultrasonography (USG) has several advantages (i.e., inexpensive, convenient, dynamic, radiation-free) over direct radiographic imaging, and it is widely used for musculoskeletal conditions, particularly in the shoulder region. [12,13] Furthermore, it has been shown to be a valid and reliable method for the assessment of the GHS in post-stroke patients.…”
mentioning
confidence: 99%